The Use of Organic and Anorganic and Mulch on Zucchini (Cucurbita pepo L) Plant with Elephant Manure from Borobudur Tample - Pramono Hadi; Firda Rizkian; Tri Rahayu (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2021)
This study aims at identifying the use of organic and anorganic mulch of the zucchini plants appropriate elephant manure inyorder to obtain optimal growth and yield. The study has been on, Boyolali Regency with an altitude of 170 m above sea level.Thishresearch method is an experiment using a factorial treatment Randomized Completed Block Design (RCBD) with 3 times. There are two kinds of treatment under the study that is dose of elephant manure and kind of mulch, elephant manure dose treatment factor (G), there are 3 levels of treatment, namely (G1) Elephant manure dose 5 tons / ha, (G2) Elephant manure dose 10 tons / ha, (G3) The dose of elephant manure is 15 tons / ha, the treatment factor is mulch (M), there are 3 types of treatment, namely (M0) without mulch (M1) Silver mulch (M2) mulch straw.Therresults of this study show that treatment for the dose of elephant manure (G) showed no significant different to all observed parameters, the mulch type treatment (M) show highly significant to fruituweightoperlplantmand fruit diameter, show significant to fruit length, and biomassyfreshpweight per plant, while biomasydry weight per plant showed no significant effect. The interaction between elephant manure dose and mulch type (GxM) showed no significant to all observed parameters. The highest fruit weight yield was (478.84 g) in the treatment combination and the lowest was obtained in the treatment combination (253.05 g).